2014
DOI: 10.1002/jsfa.6894
|View full text |Cite
|
Sign up to set email alerts
|

Eating quality of meat from six lamb breed types raised in Brazil

Abstract: Under the conditions evaluated in this study, meat from Dorper/SI and Hampshire Down cross-breeds showed better eating quality, satisfying most consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
5
2
1
Order By: Relevance
“…McPhee et al (2008) also agreed that genotype had an impact on intramuscular fat accretion in the Longissimus muscle when they compared fat levels of five sheep breeds during growth. Contrary to the results showed in this study, (Monaco et al, 2014) reported that no significant differences were found in meat moisture, protein, fat and ash contents of six lamb breed types raised in Brazil. Table 2 showed the chemical and physical properties of the meat obtained from the three breeds.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…McPhee et al (2008) also agreed that genotype had an impact on intramuscular fat accretion in the Longissimus muscle when they compared fat levels of five sheep breeds during growth. Contrary to the results showed in this study, (Monaco et al, 2014) reported that no significant differences were found in meat moisture, protein, fat and ash contents of six lamb breed types raised in Brazil. Table 2 showed the chemical and physical properties of the meat obtained from the three breeds.…”
Section: Resultscontrasting
confidence: 54%
“…Contrary to the results here, Yousefi et al, (2012) showed significant differences between sheep breeds in shear force. This was also the case with the results projected by Monaco et al, (2014).…”
Section: Resultsmentioning
confidence: 53%
“…Usually, production of sheep meat does not meet the consumer expectations because carcasses are not standardized and contain excess of fat . The causes for unpleasant odour and flavour characteristics of ruminant meat have been extensively revised and it is believed to be due to the high proportion of saturated fatty acids (FAs), in addition to the degradation and reactions of water‐soluble compounds during cooking . Moreover, the flavour intensity of lamb meat is related with the proportion of intramuscular fat (IMF) and subcutaneous fat, both of which increase with slaughter age.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors limit sheep breeding to play a more significant role on rural development and become a source of financial income in developing countries such as Brazil [ 2 , 3 ]. The success of sheep farming will rely on tackling different issues that configure bottlenecks which are scattered throughout the production chain and require urgent attendance.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of meat has been an important subject [ 3 ], including topics related to breed or consumer preferences [ 3 , 6 ]. Regarding different age categories of sheep (which may be bred in separate groups) the demands are greater for meat originated from lambs.…”
Section: Introductionmentioning
confidence: 99%